Family support for visually impaired middle - schoolers An applied study in a school for visually impaired children - THAMER MABROUK – M’sila - zenidi, Nabila (Al-Jamie Journal In Psychological Studies and Educational Sciences, 2021)
In the current study, we addressed the subject of family support for visually impaired middle - scholars, because of its importance in their lives and the impressive results that they can achieve if it is available, especially at this critical age and this is what drew our attention during our work at the school for visually impaired children through psychological follow-up to them and their families. as well as through the review of various research and studies in this field, which proved that the visually impaired suffer from many behavioral, emotional and relational problems due to their disability on the one hand and the social outlook and constraints or restrictions imposed on them on the other hand .In addition to the physiological and psychological changes imposed by adolescence, which requires their great need for support, especially from those closest to them and the first environment in which they grew up, which is better to provide the greatest support to them, which made us conduct this study through which our goal is to know the level of family support for the visually impaired middle-schoolers, as well as the detection of differences between the sample members in the family support according to the gender variable (male-female).and the severity of disability (total –partial). and to achieve these goals was relied on the family support scale of Dr. Vivian Khamis and after confirming the psychometric characteristics of the instrument by applying-Thamer Al-Mabrouk-wilaya m’sila for the academic year 2019/2020 (01 October-15 December 2019)., Relying on the appropriate descriptive approach which adopted for the nature of the study and after applying statistical methods through the program of statistical packages for social studies to analyze the responses of the sample members, using repetitions, arithmetic mean, Persson correlation coefficient and Test-t-. The results of the study have yielded the following: - The level of family support among visually impaired adolescents is average - There are no significant differences at the level of significance (Alpha=0.05). in family support among visually impaired middle-schoolers attributable to the gender variant. - There are no significant differences at the level of significance (Alpha=0.05). in family support among visually impaired middle-schoolers due to the variable severity of disability.